2004
DOI: 10.1055/s-2004-832898
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor-mediated inhibition of the hypothalamic-pituitary-adrenal axis in aged humans

Abstract: In aged humans, diminished mineralocorticoid receptor (MR)-mediated feedback in the brain could contribute to impaired feedback regulation of the hypothalamic-pituitary-adrenal (HPA) axis, but no study specifically compared young and old individuals with regard to MR function. We examined 10 healthy young (mean age 6 SD [standard deviation] 26.1 6 2.9 years) and 10 elderly men (68.3 6 4.7 years) at the nadir of cortisol levels (2:00 PM-9:00 PM) when HPA activity is mainly controlled by the MR. After pretreatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…It has been demonstrated that the hippocampal MRs display an important role in the glucocorticoid-mediated feedback control of HPA axis (3,11), and it is assumed that they mediate the 'proactive' feedback, which maintains the basal HPA activity, mainly at the nadir of the circadian rhythm (4,12). These findings are supported by studies indicating significant occupations of hippocampal MRs (50-70%) during the nadir of glucocorticoid secretion, while GRs are less occupied during the nocturnal nadir (13)(14)(15)(16). The functional role of MRs is proposed to proceed through tonic inhibitory projections to the paraventricular nucleus (PVN) of the hypothalamus (17)(18)(19)(20).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…It has been demonstrated that the hippocampal MRs display an important role in the glucocorticoid-mediated feedback control of HPA axis (3,11), and it is assumed that they mediate the 'proactive' feedback, which maintains the basal HPA activity, mainly at the nadir of the circadian rhythm (4,12). These findings are supported by studies indicating significant occupations of hippocampal MRs (50-70%) during the nadir of glucocorticoid secretion, while GRs are less occupied during the nocturnal nadir (13)(14)(15)(16). The functional role of MRs is proposed to proceed through tonic inhibitory projections to the paraventricular nucleus (PVN) of the hypothalamus (17)(18)(19)(20).…”
Section: Introductionsupporting
confidence: 79%
“…There is also evidence that MR antagonists enhance the ACTH, cortisol, and DHEA responses to both CRH and AVP stimulations, thus indicating that the stimulatory effect of MR blockade is probably mediated by concomitant modulation of both CRH and AVP (5,23,29). On the other hand, the administration of a strong MR agonist, fludrocortisone, exerted a significant inhibitory effect on spontaneous cortisol levels during the nadir of the circadian rhythm (31), and abolished the stimulatory effect of metyrapone on ACTH and 11-deoxycorticosterone in humans (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In rats and dogs it has been shown that MR expression in the hippocampus is reduced in aged animals (Rothuizen et al, 1993;Yau et al, 2002). Consistent with these findings, aged humans showed diminished MR-mediated inhibition on cortisol secretion (Heuser et al, 2000a, b;Otte et al, 2003). Thus, diminished MR expression may contribute to cognitive deficits in aging and depression.…”
Section: Discussionmentioning
confidence: 67%
“…Although the above hypothesis is still highly speculative at this point in time, the recent recurrence of the hormesis hypothesis calls for more and more studies assessing the effects of different levels of MRs and/or GRs on the hermetic zone. At this point in time, it is quite difficult to assess the existence of down-regulation of either MRs and GRs in humans, although various neuroendocrine challenge studies provide solid evidence of downregulation of these receptor types in humans (Otte et al, 2003). Moreover, other studies report the presence of down-regulation of hippocampal GRs during opiate withdrawal in rodents (McNally and Akil, 2003), during amygdala kindling (Kalynchuk & Meaney, 2003), in schizophrenia and mood disorders in humans (Webster et al, 2002), and after chronic exposure to stress (Henry et al, 1994;Barbazanges et al, 1996;Levitt et al, 1996;Welberg et al, 2000).…”
Section: Hormetic Effects Of Glucocorticoids On Human Memory 45mentioning
confidence: 99%